Pengaruh Metode Latihan dan Penggunaan Media Video Terhadap Kecepatan Reaksi Atlet Bola Voli - Khaniful Adib; Rudy Sumiharsono; Eges Triwahyuni (LP. Ma'arif Janggan Magetan, 2023)
The problem in this research is whether there is an influence of training methods and the use of video media together on the reaction speed of teenage volleyball athletes in Class 1) serve under, 2) pass under, 3) pass over. Variable stalk muscle. Causal quantitative research design. The method of determining the purposive sampling area. Population research technique population research. Data collection techniques: 1). observation, 2). interview, 3). document, 4) questionnaire, 5). test. Data analysis 1) instrument test, 2) classic assumption test, 3) hypothesis test. The results of the t test on reaction speed (0.737>0.682), the t test of the use of video media on reaction speed (0.855>0.682), the results of the F test of t test of training methods and the use of video media on reaction speed (11.384>2.87). So it can be concluded that the training method and video media have an effect on reaction speed so that H0 is rejected.